Interpretasi dan Strategi Kesadaran Tubuh sebagai Konsep Memahami (Individu Interpretation and Body Awareness Strategies) - Mirna Ari Mulyani (Wardah, 2016)
Abstract: A counselor should uphold the principle of secrecy during and after the counseling process ends. A counselor is not authorized to publish the results of talks counseling to anyone without the permission of the counselee. If a counselor does not maintain data confidentiality counselees or talk during the counseling process, then a counselor had violated the code of ethics of guidance and counseling. And it was fatal for professions in the middle cloth (counselor). Therefore, the article focused on the interpretation and body awareness strategy in one strategy both individual and group counseling.